The theory of measurements - Tuttle, Lucius, 1877- (Heritage., 1946)
This book introduces some of the applications of the exact sciences and their relation to the ""practical"" sciences and useful arts for math students and emphasizes general considerations of measurement, theory of errors, general methods of procedure, quantitative accuracy, adjustment of observations, etc. for physics students.